2015
DOI: 10.1590/1414-431x20154397
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of swimming exercise influences aortic reactivity in rats

Abstract: Exercise is known to cause a vasodilatory response; however, the correlation between the vasorelaxant response and different training intensities has not been investigated. Therefore, this study evaluated the vascular reactivity and lipid peroxidation after different intensities of swimming exercise in rats. Male Wistar rats (aged 8 weeks; 250-300 g) underwent forced swimming for 1 h whilst tied to loads of 3, 4, 5, 6, and 8% of their body weight, respectively (groups G3, G4, G5, G6 and G8, respectively; n=5 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
13
2
Order By: Relevance
“…In the spontaneous hypertension rats (SHR), exercise normalizes the increased collagen deposition and diminished fenestra size in the internal elastic lamina, meaning that exercise shows the benefit roles in normalizing the increased vascular stiffness and decreased vascular distensibility in both small mesenteric arteries and coronary arteries [48]. However, high-intensity exercise leads to the opposite effects that increased oxidative stress, elevated blood pressure, and high vasoconstrictor activity are found [49]. Some studies report that males tend to achieve greater reductions than females from the exercise training [50].…”
Section: Mechanisms Of Action For Physical Exercisementioning
confidence: 99%
“…In the spontaneous hypertension rats (SHR), exercise normalizes the increased collagen deposition and diminished fenestra size in the internal elastic lamina, meaning that exercise shows the benefit roles in normalizing the increased vascular stiffness and decreased vascular distensibility in both small mesenteric arteries and coronary arteries [48]. However, high-intensity exercise leads to the opposite effects that increased oxidative stress, elevated blood pressure, and high vasoconstrictor activity are found [49]. Some studies report that males tend to achieve greater reductions than females from the exercise training [50].…”
Section: Mechanisms Of Action For Physical Exercisementioning
confidence: 99%
“…Some studies have demonstrated that moderate to high-intensity ET provides greater benefits to cardiovascular and pulmonary functioning than lower intensity activities [35]. On the other hand, other studies reported vascular damage induced by the practice of high-intensity ET, such as a reduction in antioxidant enzymes, increase in contractility, and impairment of the relaxation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…They were acclimated 1 week before exercise, being subjected to periods of 10, 10, and 30 min of swimming exercise, three times a week during 1 week, in intercalated days, according to the protocol adapted from Chibalin et al ( 2000 ). The swimming protocol was adapted from Chies et al ( 2003 ) and Brito et al ( 2015 ). Briefly, the animals were submitted to forced swimming for 1 h with a metal of 3% of their body weight attached to them, to improve the animal's resistance and avoid floating in water, however maintaining the aerobic exercise as moderate intensity (Brito et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The swimming protocol was adapted from Chies et al ( 2003 ) and Brito et al ( 2015 ). Briefly, the animals were submitted to forced swimming for 1 h with a metal of 3% of their body weight attached to them, to improve the animal's resistance and avoid floating in water, however maintaining the aerobic exercise as moderate intensity (Brito et al, 2015 ). The exercise was performed in a plastic container measuring 43 cm width, 63 cm length, and 33 cm depth, with water at 24–27°C.…”
Section: Methodsmentioning
confidence: 99%